Secondary cameras onboard the Mini-EUSO experiment: Control software and calibration. Issue 5 (1st September 2019) - Turriziani, S.; Ekelund, J.; Tsuno, K.; Casolino, M.; Ebisuzaki, T.
Abstract: Mini-EUSO is a space experiment selected to be installed inside the International Space Station. It has a compact telescope with a large field of view (44 × 44 sq. deg.) focusing light on an array of photo-multipliers tubes in order to observe UV emission coming from Earth's atmosphere. Observations will be complemented with data recorded by some ancillary detectors. In particular, the Mini-EUSO Additional Data Acquisition System (ADS) is composed by two cameras, which will allow us to obtain data in the near infrared, and in the visible range. These will be used to monitor the observation conditions, and to acquire useful information on several scientific topics to be studied with the main instrument, such as the physics of atmosphere, meteors, and strange quark matter. Here we present the ADS control software developed to stream cameras together with the UV main instrument, in order to grab images in an automated and independent way, and we also describe the calibration activities performed on these two ancillary cameras before flight.